Supervising Teachers’ Insight in Developing Motivation and Confidence of Pre-Service English Teachers During Teaching Practicum - Indrawati Indrawati; Anna Musyarofah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Pre-Service English Teachers (PSTs) of Tarbiyah Fakulty of IAIN Syaikh Abdurrahman Siddik Bangka Belitung do their teaching practicum at high schools. Their supervising teachers play important role in evaluating, couching and mentoring them. In order to develop PSTs motivation and confidence during teaching and learning process, this study was conducted. Some supervising teachers from some high schools in Bangka regency and Pangkalpinang were interviewed. And the findings showed that PSTs should learn more about lesson planning, classroom management, and speaking skills. The result of the interviewed also gave a brief explanation about some subjects and courses that must be equipped by PSTs before they have their teaching practicum at schools.